2020
DOI: 10.1123/ijsnem.2019-0090
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Carbohydrate-Electrolyte Beverage Does Not Improve Glucose Availability, Substrate Oxidation, Gastrointestinal Symptoms or Exercise Performance, Compared With a Concentration and Nutrient-Matched Placebo

Abstract: The impact of a carbohydrate-electrolyte solution with sodium alginate and pectin for hydrogel formation (CES-HGel), was compared to a standard CES with otherwise matched ingredients (CES-Std), for blood glucose, substrate oxidation, gastrointestinal symptoms (GIS; nausea, belching, bloating, pain, regurgitation, flatulence, urge to defecate, and diarrhea), and exercise performance. Nine trained male endurance runners completed 3 hr of steady-state running (SS) at 60% , consuming 90 g/hr of carbohydrate from C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 40 publications
4
38
0
Order By: Relevance
“…Our data do not support this proposition. Instead, they support previous observations made in thermoneutral environments during running (McCubbin et al 2019;Barber et al 2020) and cycling (Baur et al 2019;Mears et al 2020a), which reported no differences in blood glucose concentrations, substrate oxidation, or exercise performance between the two drink mixtures.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our data do not support this proposition. Instead, they support previous observations made in thermoneutral environments during running (McCubbin et al 2019;Barber et al 2020) and cycling (Baur et al 2019;Mears et al 2020a), which reported no differences in blood glucose concentrations, substrate oxidation, or exercise performance between the two drink mixtures.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study we report high rates of severe GI discomfort (GI scores over 5) in both the MAL+FRU+PEC+ALG (71%) and MAL+FRU (57%) trials relative to water (36%). We can therefore be confident that our protocol induced substantial GI distress during each experimental trial relative to previous investigations using both runners (McCubbin et al 2019;Barber et al 2020) and cyclists (Baur et al 2019;Mears et al 2020a), and increases the likelihood of detecting a difference between CHO drinks. We did note that sensations of gut discomfort were greater following MAL+FRU+PEC+ALG as compared to both the MAL+FRU and WATER.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This finding is in accord with a recent study where ingestion of a 500 mL bolus of a 18% carbohydrate drink containing 0.4 g pectin and 0.6 g of alginate resulted in 1.8 and 2.4 times faster gastric half-emptying time compared to an isoenergetic MD+FRU drink and a glucose+FRU drink, respectively (42). Recent studies have found no difference in total substrate oxidation and blood glucose concentrations (43)(44)(45) or exogenous carbohydrate oxidation (46) with the addition of sodium alginate and pectin in drinks matched for maltodextrin and fructose content during exercise.…”
Section: Exogenous Carbohydrate Oxidationsupporting
confidence: 88%